Antibiotic resistance in waste water and surface water and human health implications - Célia M. Manaia (2012)
The utilization of antibiotics to control infectious diseases is one of the biggest advances in human and veterinary health care. However, the generalized use of antibiotics has been accompanied by a worrisome increase in the prevalence of antibiotic-resistant bacteria. This evidence motivated numerous studies on the diversity and distribution of antibiotic-resistant bacteria and resistance genetic determinants not only in clinic but also in different environmental compartments. Given the particular importance that the anthropic water cycle (waste water/surface water/drinking water) may have in the development and dissemination of antibiotic-resistant organisms, this chapter aims at summarizing the recent advances in this area. Sections 1 and 2 are an Introduction to antibiotic resistance, summarizing some mechanisms and modes of resistance acquisition. In Sect. 3, the contribution of the environmental pollution and other anthropic pressures for antibiotic resistance evolution is discussed. The use of different methodologies and the limitations to achieve general conclusions on the characterization and quantification of antibiotic resistance in aquatic environments are examined in Sects. 4 and 7. Sections 57 summarize recent evidences on the widespread distribution of antibiotic resistance in different compartments of the anthropic water cycle. The scarcity of studies giving evidences on the direct effect of anthropic pressures on antibiotic resistance acquisition and maintenance in treated waste/drinking waters is highlighted. The contribution of bacterial community rearrangement, imposed by water treatment processes, on the increase of antibiotic resistance is discussed.